The Effectiveness of Graphic Organizer to Teach Reading Viewed from Students’ Motivation - Fitri Nurdianingsih (Jurnal Penelitian Pendidikan, 2014)
The objective of the research is to identify whether or not: (1) Graphic Organizer is moreeffective than Lecture to teach reading; (2) students who have high motivation have betterreading skill than those who have low motivation; and (3) there is an interaction effectbetween teaching methods and the students’ motivation on the students’ reading skill. Theresearch was conducted in IKIP PGRI Bojonegoro, East Java. The research was conductedfrom March to May 2014. The method used for the research was experimental study. Thepopulation of the research was the fourth semester students of IKIP PGRI Bojonegoro. Thesampling used was cluster random sampling. The sample of the research was two classes,they were experimental class taught using Graphic Organizer and control class taught usingLecture. The instruments used to collect the data were students’ motivation questionnaire inthe form of likert scale and reading test in the form of multiple choice. Meanwhile, to analyzethe data, Multifactor Analysis of Variance (ANOVA) test 2 x 2 and Tukey test were used. Thedata analysis shows the following findings: (1) Graphic Organizer is more effective thanLecture to teach reading for the fourth semester students of IKIP PGRI Bojonegoro; (2) thestudents who have high motivation have better reading skill than those who have lowmotivation; and (3) there is an interaction between teaching methods and students’motivation to teach reading at the fourth semester students of IKIP PGRI Bojonegoro. Basedon the research findings, it can be concluded that Graphic Organizer is an effectivetechnique to teach reading for the fourth semester students of English Education Department,IKIP PGRI Bojonegoro, in the academic year 2013/2014. The effectiveness of this techniqueis affected by students’ motivation level.